Identification of Tinomiscium petiolare from Vietnam using the DNA barcode - B. B. Thinh; R. V. Doudkin; L. D. Chac; H. V. Chinh; Q. V. Hoi; N. T. Lien (Труды по прикладной ботанике, генетике и селекции)
Background. Tinomiscium petiolare Hook.f. & Thomson is a medicinal species of the family Menispermaceae. This species is currently being intensively exploited for therapeutic purposes. Precise and rapid identification of T. petiolare is critical and essential for the classification, propagation, use and conservation of its genetic resources. In recent years, DNA barcoding has been known to be a fast and sensitive method for identifying species at any stage of development, using short DNA sequences. In this study we have performed the identification of T. petiolare specimens in Vietnam based on the sequence analysis of 4 DNA barcode loci: ITS, matK, rbcL and rpoC.Materials and methods. Total DNA was extracted from leaf samples using DNeasy Plant Mini Kit. PCR amplification of the ITS, matK, rbcL and rpoC regions was carried out on the GeneAmp PCR System 9700 with specific primers. The purified PCR products were sequenced on the ABI 3500 Genetic Analyzer system, using BigDye®Terminator v3.1 Cycle Sequencing Kit. These genetic sequences were analyzed and compared, and a phylogenetic tree was constructed using BioEdit, BLAST, and MEGA 6 programs.Results and conclusion. The success rate of amplification and sequencing was 100% for all 4 DNA barcode loci (ITS, matK, rbcL and rpoC) in the studied specimens. The produced sequence sizes of ITS, matK, rbcL and rpoC in the specimens were 574 bp, 810 bp, 527 bp and 488 bp, respectively. Further, we identified that all studied specimens were genetically related to each other and associated with the same species T. petiolare. Overall, the results of the study generated the most complete DNA barcode database of T. petiolare collected in Vietnam, contributing to the taxonomy and identification of this species.